Exploiting unconventional prokaryotic hosts for industrial biotechnology. Issue 4 (April 2022) - Blombach, Bastian; Grünberger, Alexander; Centler, Florian; Wierckx, Nick; Schmid, Jochen
Abstract : Developing cost-efficient biotechnological processes is a major challenge in replacing fossil-based industrial production processes. The remarkable progress in genetic engineering ensures efficient and fast tailoring of microbial metabolism for a wide range of bioconversions. However, improving intrinsic properties such as tolerance, handling, growth, and substrate consumption rates is still challenging. At the same time, synthetic biology tools are becoming easier applicable and transferable to nonmodel organisms. These trends have resulted in the exploitation of new and unconventional microbial systems with sophisticated properties, which render them promising hosts for the bio-based industry. Here, we highlight the metabolic and cellular capabilities of representative prokaryotic newcomers and discuss the potential and drawbacks of these hosts for industrial application. Highlights: Changing economic and environmental constraints call for the exploitation of novel microbial systems in industrial biotechnology. Multi-factorial traits like tolerance, growth efficiency, or handling cannot always be engineered into existing model organisms. Microbes with superior intrinsic properties compared to conventional employed cell factories are a more promising route to master future challenges in the bioeconomy. We present key criteria that microbial newcomers have to meet in order to achieve industrial relevance.